Bone fracture in severe small-for-gestational-age, extremely low birth weight infants: A single-center analysis. (March 2017) - Maruyama, Hidehiko; Amari, Shoichiro; Fujinaga, Hideshi; Fujino, Shuhei; Nagasawa, Junko; Wada, Yuka; Tsukamoto, Keiko; Ito, Yushi
Abstract: Introduction: Bone fracture is a complication of extremely low birth weight infants (ELBWIs). This study aimed to analyze risk factors for bone fracture in a population of severe small-for-gestational-age (SGA) ELBWIs. Methods: We retrospectively studied data from ELBWIs with a birth weight < 1000 g and <− 2 standard deviations (SDs) born at the National Center for Child Health and Development, Japan, from 2013 to 2015. Infants were divided into fracture and control groups. Serum calcium (Ca) and phosphorus (P) levels, perinatal factors, and previously reported risk factors were analyzed. Results: Of 25 cases of severe SGA ELBWIs, 5 cases of bone fracture were identified. Gestational age was 27.7 ± 2.2, 29.1 ± 2.6 weeks (mean difference [MD] − 1.4, 95% confidence interval [CI]: − 4.0, − 1.2, p = 0.280), birth weight (BW) 448 ± 105, 673 ± 216 g (MD − 225, 95% CI: − 433, − 17, p = 0.036) and BW-SD − 4.1 ± 0.1, − 3.4 ± 0.8 (MD − 0.8, 95% CI: − 1.5, − 0.02, p = 0.045) in the fracture and control groups, respectively. Minimums of serum Ca and P were 6.6 ± 1.4, 8.1 ± 0.8 mg/dl (MD − 1.5, 95% CI: − 2.5, − 0.6), p = 0.003) and 2.3 ± 0.6, 3.5 ± 1.1 mg/dl (MD − 1.2, 95% CI: − 2.2, − 0.1, p = 0.027) in the fracture and control groups, respectively. Conclusion: Lower BW and BW-SD were possible risk factors for bone fracture. Hypocalcemia and hypophosphatemia may also contribute to the condition. Highlights: We focused on the trend of serum calcium and phosphorus in ELBWIs, and analyzed the risk factors for bone fracture. Lower BW and BW-SD were found to be possible risk factors for bone fracture. Hypocalcemia and hypophosphatemia may also be contributing factors to the condition.